Social Policies and Structural Reforms in Europe - Ferran Brunet Cid; Mar López Rancaño (Romanian Journal of European Affairs)
This paper considers the social and structural policies in contemporary Europe. The presentation is organized in four sections. First, we discuss the emerging Europe, the new unity based on democracy and the market economy, the special European Union formula, and comparisons with America. Second, we analyze the dynamics of the European economy, the convergence process, the gaps between United States in productivity and standard of living, competitiveness issues, and the emergence of a new European economy and new European policy mix. Third, we consider European social conditions, the stationary and aging population, Europe’s low employment rate and permanently high unemployment. European economic growth could draw on two major sources: the labor reserves and reforms in factor, product and service markets. In a monetary union, advanced industrial relations should promote labor mobility and salary flexibility. The social security systems permit the redistribution and cohesion which defines the European model. Fourth, for the new Europe, the structural reform strategy is the way forward for the challenge of European economic policy and social policy: more and better jobs thanks to sustainable growth in a dynamic and competitive knowledge-based economy, favoring greater social cohesion.